Adoption of Animal Traction Technology in the Builsa District of Upper East Region of Ghana - Akpeintuik, C.A. (University of Ghana, 2003)
The Builsa district is a peasant farming community. It had a problem of recurrent food shortage. The use of animal traction was one of the suggested solutions to this problem, hence its introduction in 1937. Reports suggested its low adoption. The study was to verify the veracity and the causes of the low adoption. A conceptual framework was developed. The concepts include: the farmers' sieve system, characteristics of animal traction technology and environmental influences. Adoption was found to be high (91%). At 5% significant level, the Fisher exact two-tailed test showed no significant difference by ages, family size, ownership of donkeys, credit received, use of lecture method of training, demonstration/lectures and demonstration/group discussion categories and adoption. Those variables that showed significant difference include ownership of cattle, farm size, those who received training in AT, those who received training through demonstration alone and those who received training through group discussion alone. It is recommended that when introducing a new technology into a peasant farming community like the Builsa District beneficiaries should express the need for the technology. Traditional leaders should be involved. Financial institutions should get to the doorsteps of farmers and educate them, on how to access credit facilities. Further research should look into the effects of the use of AT on the environment and schooling in the study area.
Thesis(M.Phil)-University of Ghana, 2003